The Prisoner's Dilemma: An Adequate Concept for Ethical Analysis in Healthcare? A Systematic Search and Critical Review - Wolf Rogowski; Oliver Lange (Journal of Business Ethics, 2020)
Schools of economic ethics inspired by Buchanan propose viewing ethical conflicts as prisoners' dilemmas (PDs) to facilitate solutions based on Pareto-improving institutional changes. Given that healthcare is determined by complex institutional arrangements, it has been claimed that this approach is also suitable for business ethics in healthcare. To scrutinize this claim, this research systematically searched for studies reporting PD structures in healthcare. PubMed, EconLit, and EconBiz were searched to find articles in German and English. Study type, characteristics of the game, and the proposed means to overcome the dilemma (if mentioned) were extracted and analyzed for aspects supporting or challenging the claim. Across 53 studies, 68 descriptions of various dilemmas in healthcare and public health were identified. Many authors successfully developed proposals for institutional change to overcome these dilemmas. However, many of these analyses exhibited limitations such as oversimplifications or inconsistencies. Also, the quality of evidence on both the characteristics of dilemmas and the effectiveness of proposed solutions was very poor. The subsamples of studies that explicitly cited the ethical approach were disjunct from those that applied empirical methods to analyze the dilemmas (frequently applying empirically richer frameworks than rational choice only). The large number of identified PDs indicates that economic ethics is relevant to healthcare. However, there is a need for further evidence to substantiate both the descriptive and prescriptive claims of this ethical theory. It should thus be seen as a complement that needs justification, rather than a substitute superior to other ethical frameworks.
Keywords: 300; Prisoner's dilemma; Healthcare; Systematic review